Low temperature molten salt preparation of molybdenum nanoparticles. (January 2016) - Huang, Zhong; Liu, Jianghao; Deng, Xiangong; Zhang, Haijun; Lu, Lilin; Hou, Zheng; Zhang, Shaowei
Abstract: Pure molybdenum (Mo) nanoparticles (NPs) were synthesized by a novel molten salt technique using Na2 MoO4 and Al as starting materials and NaCl, KCl and NaF to form a reaction medium. The effects of salt type, reaction temperature and salt to reactant ratio on the synthesis of Mo NPs were investigated in detail. Phase pure Mo NPs with a crystalline size of about 46 nm were synthesized at as low as 650 °C which was much lower than that required by other conventional reduction methods. Among the salts tested, the NaClKClNaF ternary salt showed the best accelerating effect on the low temperature Mo NPs formation, and the optimal weight ratio of salt to reactant was 1.0:1.0. The "dissolution-precipitation mechanism" played a dominant role in the molten salt synthesis of Mo NPs. Graphic abstract: Mo nanoparticles (NPs) with a grain size of 46 nm are prepared at 650 °C for 2 h by molten salt synthesis and for the first time, the temperature was at least 150 °C lower than that required by conventional hydrogen or carbothermal reduction method. Highlights: Phase pure Mo NPs were synthesized at as low as 650 °C by molten salt synthesis. The formation temperature was at least 150 °C lower than that by other methods. Mo NPs exhibited a narrow size distribution between 30 and 120 nm. Mo dendritic rods were found for the first time.